O zbirki Zbrana dela slovenskih pesnikov in pisateljev - Kramberger, Igor (Slavistična revija, 2013)
The point of departure for this study is a booklet by Matija Ogrin, the third editor-in-chief of the series Zbrana dela slovenskih pesnikov in pisateljev (The Complete Works of Slovene Poets and Prose Writers), which he prepared as an aid to editors of individual volumes. In certain instances, I indicate the history of evaluating and selecting writers for the series. I also point out the changed status of editors of such publications. This is the basis for a proposal to compile a handbook containing the analytical suppositions of bookspublished in the series, as well as details on the materials in the commentaries and their arrangement in short the scholarly apparatus of each book.
Keywords: knjižne zbirke; Slovene literature; slovenska književnost; slovenski pesniki; slovenski pisatelji; vrednotenje; zbrana dela; Zbrana dela slovenskih pesnikov in pisateljev